KEMAMPUAN KEPEMILIKAN INSTITUSIONAL MEMODERASI PENGARUH EARNING POWER, LEVERAGE, DAN UKURAN PERUSAHAAN TERHADAP MANAJEMEN LABA - Raka Raka; Sugi Suhartono (Sekolah Tinggi Ilmu Ekonomi Wiyatamandala, 2018)
This study aims to determine whether earnings power, leverage, and firm size affect earnings management and whether institutional ownership moderate the effect of earning power, leverage, and size of the company on earnings management. The theory underlying this research is agency theory and positive accounting theory. Based on both theories, the conflict of interest that occurs between the owner and the manager where each will tend to emphasize personal interests or certain parties. The sample in this study consists of 93 manufacturing companies listed on the Indonesia Stock Exchange for the period 2014-2016. Sampling was done by purposive sampling method. The data analysis technique used to test the hypothesis is Moderated Regression Analysis. The results of this study indicate earnings power, leverage, and firm size have a positive effect on earnings management. Institutional ownership weakens the effect of earning power on earnings management. Keywords : Earning management, earning power, leverage, company size